Improving Digital Financial Literacy of Rural MSMEs Actors through Socialization of the Kledo Application - Faizah Khaeruddin; Maya Kasmita; Andi Muhammad Rivai; Nurul Aliah; Asmaul Husnah Nasrullah (PT. Global Research Collaboration, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Su'rulangi Village face challenges in financial management caused by low financial literacy and minimal use of technology. The community service program aims to improve the financial literacy of MSME actors through the use of free financial recording applications. The methods used include an initial survey; training planning and preparation; training implementation; and training evaluation. The results of the program in the long and short term show a significant increase in the understanding and use of digital financial applications, which contributes to better financial management. Although there are obstacles such as limited internet access and changes in habits, development opportunities through regular mentoring and improving internet infrastructure are identified as important steps for the sustainability of the program.